2000
DOI: 10.1093/ajcn/71.6.1705s
|View full text |Cite
|
Sign up to set email alerts
|

Protection against breast cancer with genistein: a component of soy

Abstract: Breast cancer is the most common cancer in women. Because genetics is believed to account for only 10-15% of breast cancer cases, the environment, including nutrition, is thought to play a significant role in predisposing women to this cancer. Studies of Asian women suggest that those who consume a traditional diet high in soy products have a low incidence of breast cancer, but that among emigrants to the United States, the second generation, but not the first, loses this protection. These findings suggest a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
157
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(162 citation statements)
references
References 17 publications
2
157
0
3
Order By: Relevance
“…They are an integral component of the human diet and are believed to provide a number of health benefits to adults, including chemoprevention leaves [105][106][107][108][109][110][111][112]. Bioflavonoids have a variety of effects on human cells.…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are an integral component of the human diet and are believed to provide a number of health benefits to adults, including chemoprevention leaves [105][106][107][108][109][110][111][112]. Bioflavonoids have a variety of effects on human cells.…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
“…Bioflavonoids have a variety of effects on human cells. They represent the most abundant natural source of antioxidants, potently inhibit tyrosine kinases, and exhibit anti-proliferative and pro-apoptotic affects leaves [105][106][107][108][109][112][113][114][115][116]. However, they also display cytotoxic and genotoxic properties and many are potent topoisomerase II poisons [117][118][119][120].…”
Section: Non-covalent Topoisomerase II Poisonsmentioning
confidence: 99%
“…The protective effect of soybean might also be due to its content of isoflavones, like genistein, which are believed to have a potential role in reducing tumor incidence (Hacker et al, 1998). These isoflavones have been reported to reduce the risk of breast cancer (Messina, 1999;Lamartiniere, 2000) and urinary tract cancer (Su et al, 2000) in animal studies. Lee et al (1995) reported that soybean isoflavones may have an anticarcinogenic effect by suppressing the early stages of hepatocarcinogenesis induced by diethylnitrosamine.…”
Section: Discussionmentioning
confidence: 99%
“…During the past two decades, attention has been focused on the possible role of soybeans, which contain trypsin inhibitors, isoflavones, and phytic acid (Anderson and Wolf, 1995), on reducing or delaying the incidence of many tumors in experimental animals (Roll et al, 1980;Corasanti et al, 1982;Barnes et al, 1990;Messina and Messina, 1991;Webb et al, 1992;Anderson and Wolf, 1995;Thiagarajan et al, 1998;Appelt and Reicks, 1999;Messina, 1999;Onozawa et al, 1999;Lamartiniere, 2000;Su et al, 2000;Zaizen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…VĂĄrias alternativas Ă  terapia estroprogestativa estĂŁo sendo avaliadas, entre elas as isoflavonas, que apresentam afinidade pelos receptores de estrogĂȘnio, que seriam responsĂĄ-veis pelos seus efeitos agonistas 9 . O interesse no estudo das isoflavonas como alternativa terapĂȘutica advĂ©m de vĂĄrios estudos publicados realçando os efeitos das isoflavonas nos sintomas menopĂĄusicos 9,10 , vagina e endomĂ©trio 10,11 e na mama 10 .…”
Section: Introductionunclassified